Modelling X-ray RMS spectra II: the ultrafast outflow of PDS 456 - Härer, Lucia; Parker, M. L.; Joyce, A.; Igo, Z.; Alston, W. N.; Furst, F.; Lobban, A. P.; Matzeu, G. A.; Reeves, J. N. (Monthly Notices of the Royal Astronomical Society, 2021)
We present an improved model for excess variance spectra describing ultrafast outflows and successfully apply it to the luminous (L-bol similar to 10(47)erg s(-1)) low-redshift (z = 0.184) quasar Pico del Dias Survey (PDS) 456. The model is able to account well for the broadening of the spike-like features of these outflows in the excess variance spectrum of PDS 456, by considering two effects: a correlation between the outflow' velocity and the logarithmic X-ray flux and intrinsic Doppler broadening with v(int) = 10(4) km s(-1). Die models were generated by calculating the fractional excess variance of count spectra from a Monte Carlo simulation. We find evidence that the outflow in PDS 456 is structured, i.e. there exist two or more layers with outflow velocities 0.27-0.30 c, 0.41-0.49 c, and 0.15-0.20 c for a possible third layer, which agrees well with the literature. We discuss the prospects of generally applicable models for excess variance spectra for detecting ultrafast outflow's and investigating their structure. We provide an estimate for the strength of the correlation between the outflow' velocity and the logarithmic X-ray flux and investigate its validity.
CRIS-Team WoS Importer:2021-01-29

Stellar-wind variability in Cygnus X-1 from high-resolution excess variance spectroscopy with Chandra - Härer, Lucia; Parker, M. L.; El Mellah, I.; Grinberg, V.; Ballhausen, R.; Igo, Z.; Joyce, Amy; Wilms, Jörn (Astronomy & Astrophysics, 2023)
Context. Stellar winds of massive stars are known to be driven by line absorption of UV photons, a mechanism that is prone to instabilities, causing the wind to be clumpy. The clumpy structure hampers wind mass-loss estimates, limiting our understanding of massive star evolution. The wind structure also impacts accretion in high-mass X-ray binary (HMXB) systems. Aims. We aim to analyse the wavelength-dependent variability of X-ray absorption in the wind to study its structure. Such an approach is possible in HMXBs, where the compact object serves as an X-ray backlight. We probe different parts of the wind by analysing data taken at superior and inferior conjunctions. Methods. We applied excess variance spectroscopy to study the wavelength-dependent soft (2- 14 Å) X-ray variability of the HMXB Cygnus X-1 in the hard spectral state. Excess variance spectroscopy quantifies the variability of an object above the statistical noise as a function of wavelength, which allows us to study the variability of individual spectral lines. This technique was applied to high-resolution gratings spectra provided by Chandra, accounting for various systematic effects. The frequency dependence is investigated by changing the time binning. Results. The strong orbital phase dependence we observe in the excess variance is consistent with column-density variations predicted by a simple model for a clumpy wind. We identify spikes of increased variability with spectral features found by previous spectroscopic analyses of the same data set, most notably from silicon in over-dense clumps in the wind. In the silicon line region, the variability power is redistributed towards lower frequencies, hinting at increased line variability in large clumps. In prospect of the microcalorimetry missions that are scheduled to launch within the next decade, excess variance spectra present a promising approach to constraining the wind structure, especially if accompanied by models that consider changing ionisation.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Accretion; accretion disks; Stars: individual: Cygnus x-1; Stars: individual: HDE 226868; Stars: winds; outflows; Techniques: spectroscopic; X-rays: binaries

The nature of the extreme X-ray variability in the NLS1 1H 0707-495 - Parker, M. L.; Alston, W. N.; Härer, Lucia; Igo, Z.; Joyce, Amy; Buisson, D. J. K.; Chainakun, P.; Fabian, A. C.; Jiang, J.; Kosec, P.; Matzeu, G. A.; Pinto, C.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
We examine archival XMM Newton data on the extremely variable narrow-line Seyfert 1 active galactic nucleus (AGN) 1H 0707-495. We construct fractional excess variance (F-var) spectra for each epoch, including the recent 2019 observation taken simultaneously with eROSITA. We explore both intrinsic and environmental absorption origins for the variability in different epochs, and examine the effect of the photoionized emission lines from outflowing gas. In particular, we show that the unusual soft variability first detected by eROSITA in 2019 is due to a combination of an obscuration event and strong suppression of the variance at 1 keV by photoionized emission, which makes the variance below 1 keV appear more extreme. We also examine the variability on long time-scales, between observations, and find that it is well described by a combination of intrinsic variability and absorption variability. We suggest that the typical extreme high frequency variability, which 1H 0707-495 is known for, is intrinsic to the source, but the large amplitude, low frequency variability that causes prolonged low-flux intervals is likely dominated by variable low-ionization, low-velocity absorption.
CRIS-Team WoS Importer:2021-12-03

X-ray emission from magnetized neutron star atmospheres at low mass-accretion rates: I. Phase-averaged spectrum - Sokolova-Lapa, Ekaterina; Gornostaev, M.; Wilms, Jörn; Ballhausen, Ralf; Falkner, Sebastian; Postnov, K.; Thalhammer, Philipp; Fürst, F.; Garcia, Javier; Shakura, N.; Becker, P. A.; Wolff, M. T.; et al. (Astronomy & Astrophysics, 2021)
Recent observations of X-ray pulsars at low luminosities allow, for the first time, the comparison of theoretical models of the emission from highly magnetized neutron star atmospheres at low mass-accretion rates (M ≤ 1015 g s-1) with the broadband X-ray data. The purpose of this paper is to investigate spectral formation in the neutron star atmosphere at low á¹€ and to conduct a parameter study of the physical properties of the emitting region. We obtain the structure of the static atmosphere, assuming that Coulomb collisions are the dominant deceleration process. The upper part of the atmosphere is strongly heated by the braking plasma, reaching temperatures of 30-40 keV, while its denser isothermal interior is much cooler (∼2 keV). We numerically solve the polarized radiative transfer in the atmosphere with magnetic Compton scattering, free-free processes, and nonthermal cyclotron emission due to possible collisional excitations of electrons. The strongly polarized emitted spectrum has a double-hump shape that is observed in low-luminosity X-ray pulsars. A low-energy "thermal"component is dominated by extraordinary photons that can leave the atmosphere from deeper layers because of their long mean free path at soft energies. We find that a high-energy component is formed because of resonant Comptonization in the heated nonisothermal part of the atmosphere even in the absence of collisional excitations. However, these latter, if present, affect the ratio of the two components. A strong cyclotron line originates from the optically thin, uppermost zone. A fit of the model to NuSTAR and Swift/XRT observations of GX 304-1 provides an accurate description of the data with reasonable parameters. The model can thus reproduce the characteristic double-hump spectrum observed in low-luminosity X-ray pulsars and provides insights into spectral formation.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Magnetic fields; Methods: numerical; Polarization; Radiative transfer; Stars: neutron; X-rays: binaries